ЎЗБЕК БОЛАЛАР ҲИКОЯЧИЛИГИНИНГ УСЛУБИЙ ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article the methodological peculiarities of histories for Anvar Obidjon  which devofed to children are analyzed